Women voters and trade protectionism in the interwar years - Alan de Bromhead (Queen's University Centre for Economic History (QUCEH), 2015)
This paper examines the lessons of the interwar period to place current concerns regarding a return to protectionism in historical context, highlighting the unique and one-time changes in voting rights that took place during the period and their relationship with trade policy. A particularly novel finding is the impact of women voters on the politics of protectionism. Public opinion survey evidence from the interwar years indicates that women were more likely to hold protectionist attitudes than men, while panel data analysis of average tariff rates during the interwar period shows that when women were entitled to vote tariffs were, on average, higher. This result is supported by an instrumental variables approach using Protestantism as an instrument for female voting rights.
Keywords: N40; N70; F50; 330; political economy; suffrage; international trade; gender differences